Reform of Decentralization of Power in Ukraine under Conditions of War: Legal Regulation, Management Features and Directions for Improvement - Chyrkin, Anton; Arsentieva, Olena; Valetska, Oksana; Antonenko , Mykhailo; Mezeria, Oleksandr (Universitas Islam Negeri Antasari Banjarmasin, 2024)
The purpose of the article is to reveal the reform of the decentralization of power in Ukraine under conditions of war. In the concept of the territorial community of Ukraine, ancient European traditions of Ukrainian local self-government and modern standards of the European Union have been successfully embodied. The productive interaction of citizens, the state, and international organizations contributed to formation of Ukrainian territorial communities. It has been proven that the personal income tax is one of the main sources of filling community budgets. For 9 months of 2022 local budgets of the Dnipropetrovsk region of Ukraine received 16,364,124 Ukrainian hryvnias (UAH) as personal income tax, which is 34% more than for the same period in 2021. Methodology: The specifics of the research subject, as well as its purpose and tasks determined the use of general scientific and special methods of scientific cognition. Stabilization and restoration of territorial communities in Ukraine require the introduction of a new three-level effective and transparent system of strategic planning: state strategy — regional strategies — community strategies. For restoration and stimulation of regional development strategizing should contain definition of the following four functional types of territories: territories of recovery, poles of economic growth, territories with special conditions for development, territories of sustainable development.